2006
DOI: 10.1103/physrevb.74.125403
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial thermal resistance between carbon nanotubes: Molecular dynamics simulations and analytical thermal modeling

Abstract: Interfacial thermal transport between offset parallel (10,10) single-wall carbon nanotubes is investigated by molecular dynamics simulation and analytical thermal modeling as a function of nanotube spacing, overlap, and length. A four order of magnitude reduction in interfacial thermal resistance is found as the nanotubes are brought into intimate contact. A reduction is also found for longer nanotubes and for nanotubes with increased overlap area. Thermal resistance between a nanotube and a reservoir at its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
270
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(289 citation statements)
references
References 57 publications
16
270
3
Order By: Relevance
“…2 and Fig. 4(a)), the thermal resistance of the cantilever and tip is given by Given the Kapitza resistance at the tip and substrate interface affects significantly SThM measurements [27,36,39,47], it must be considered to achieve a realistic model of SThM measurements. Literature estimates of Kapitza resistance values vary significantly and are not always available for the particular materials studied.…”
Section: Comparison Of Fea Simulation With Experimental Resultsmentioning
confidence: 99%
“…2 and Fig. 4(a)), the thermal resistance of the cantilever and tip is given by Given the Kapitza resistance at the tip and substrate interface affects significantly SThM measurements [27,36,39,47], it must be considered to achieve a realistic model of SThM measurements. Literature estimates of Kapitza resistance values vary significantly and are not always available for the particular materials studied.…”
Section: Comparison Of Fea Simulation With Experimental Resultsmentioning
confidence: 99%
“…Thus, the key for improving κ of CNT composites is to reduce the interfacial resistance and possibly obtain a percolation network of the highly thermally conducting CNTs. Zhong and Lukes [36] used molecular dynamics simulations to study the effect of CNT length, overlap and spacing on the interfacial resistance between two SWCNTs, and found that it decreases with increasing CNT overlap and length and decreasing inter-CNTs spacing. Within the framework of the model of Nan et al [12], we have here used the possibility to calculate the changes in interfacial resistance with temperature and pressure in a CNT-polymer composite, which have not been studied before.…”
Section: Theoretical Estimation Of κ Of Compositesmentioning
confidence: 99%
“…8,9 Individual SWNTs are known to have very high thermal conductivity, 9,10 but the thermal conductivity of SWNT networks and films is typically much lower due to the high thermal resistance of the SWNT junctions. [11][12][13] Nevertheless, the thermal conductivity of SWNT composites could be tuned over nearly four orders of magnitude by changing the alignment of the nanotubes as well as the mass density of the network (and, consequently, the density of SWNT junctions). 5,14 The ability to tune thermal conductivity in SWNT materials leads to exciting applications for heat spreaders and insulators, as well as potential thermoelectric energy harvesters.…”
mentioning
confidence: 99%
“…For the unsorted SWNT films, the temperature rise is in-between the metallic and semiconducting films, which is expected since the metallic-semiconducting nanotube junctions have higher electrical resistance and there are an "intermediate" number of metallic percolation paths in this film. 11,20 To extract the thermal conductivity of the sample, we use a finite element analysis of the 1D heat transfer equation: 21…”
mentioning
confidence: 99%